OPTIMALISASI NILAI AGAMA DAN MORAL ANAK USIA DINI MELALUI KEGIATAN BERCERITA - Titien Ruswanti; Muhammad Turhan Yani; Achmad Sya’dullah (CV. ADIBA AISHA AMIRA, 2024)
This study aims to optimize religious and moral values in early childhood through storytelling. Early childhood represents the next generation that requires character education from an early age. Early Childhood Education (PAUD) plays a crucial role in shaping children's character and morals according to religious values. The storytelling method with Islamic themes was applied in this study to enhance the development of religious and moral values in children at POS PAUD Harapan Bunda, Kampar Kiri Hilir District. The results showed that before the implementation of the storytelling method, the development of children's religious and moral values was categorized as